ANALISIS FENOMENOLOGI BUDAYA K-POP DIKALANGAN MAHASISWA UNDIKNAS DENPASAR - maria melinda (Jurnal Ilmiah Dinamika Sosial, 2018)
ABSTRACTThis study aims to determine the K-pop cultural phenomenon that occurred among Undiknas University Denpasar students. As well as analyzing the form of assimilation and the communication effect that is caused by the existence of K-pop culture in the middle of student association. This type of research is a qualitative descriptive describing the experience of students who directly feel what kind of a k- pop culture. Data source used is primary and secondary data source. In the selection of informants, the research used perposive sampling technique, the informants chosen were Undiknas students themselves. Data collection techniques used literature study techniques, observation, and interviews.This study uses Phenomenology Theory as the main theory that assess an event through real experience or experience experienced individually. The informants gave their opinions and judged what kind of a k-pop culture, after they experienced themselves as fans of K-pop culture. In addition, the informants realized there were some changes from within the self, attitude, and habits that started following Koreans. Assimilation Theory is also used in studying the changes that are particularly related to the culture and effects that arise namely the cognitive effects, affective effects, and conative effects of Korean dramas, music and products that are loved by students who love K-pop culture.Keywords: K-pop Culture Phenomenon, Cultural Blending, Phenomenology Theory.